HLA‐B*38:55Q: a new alternatively expressed allele identified in a three‐generation Italian family. (15th May 2015) - Fusco, C.; Azzarone, R.; Penta, R.; Canossi, A.; Di Iulio, B.; Toriello, M.; Auriemma, L.; Pagano, M.; Poggi, V.; Papola, F.
Summary The new allelic variant HLA‐B*38:55Q differs from the closest related B*38:01:01 by one nucleotide substitution at position 373 in exon 3 (TGC>CGC). This results in a difference of one amino acid at residue 101 of the HLA‐B heavy chain, from a neutral‐polar Cys to a basic‐polar Arg, thus impairing disulphide bridge formation in the alpha‐2 domain. This alteration of the secondary structure probably affects the maturation of the heavy chain and the level of surface expression, making the HLA‐B*38:55Q undetectable by standard serological typing.